Facets of Corporate Downsizing in Canada - Hamid, Dr. Shahnaz (IJRDO - Journal of Business Management, 2016)
This research aims to study the impact of downsizing during the recent period of recessionand slow economic growth in Canada. It furthers aims to shed light on the distinct groupsof workforce that have been significantly impacted by this process of corporatedownsizing. Downsizing has been prevalent in Canada over the past decade, mainly dueto the recession of 2008-2011 and due to the rampant use of outsourcing for cheap labor.From the results of this study it was concluded that generally government employees, lowwage workers and middle-aged male employees were the groups of workforce that weredeeply affected due to the downsizing processes and lay-offs.